High Dose Ifosfamide in Relapsed and Unresectable High-Grade Osteosarcoma Patients: A Retrospective Series - Emanuela Palmerini; Elisabetta Setola; Giovanni Grignani; Lorenzo D’Ambrosio; Alessandro Comandone; Alberto Righi; Alessandra Longhi; Marilena Cesari; Anna Paioli; Rossella Hakim; Michela Pierini; Emanuela Marchesi; et al. (Cells, 2020)
Background: The evidence on high-dose ifosfamide (HD-IFO) use in patients with relapsed osteosarcoma is limited. We performed a retrospective study to analyze HD-IFO activity. Methods: Patients with osteosarcoma relapsed after standard treatment [methotrexate, doxorubicin, cisplatin +/− ifosfamide (MAP+/−I)] with measurable disease according to RECIST1.1 were eligible to ifosfamide (3 g/m2/day) continuous infusion (c.i.) days 1–5 q21d. RECIST1.1 overall response rate (ORR) (complete response (CR) + partial response (PR)), progression-free survival at 6-month (6m-PFS), duration of response (DOR), and 2-year overall survival (2y-OS) were assessed. PARP1 expression and gene mutations were tested by immunohistochemistry and next-generation sequencing. Results: 51 patients were included. ORR was 20% (1 CR + 9 PR). Median DOR was 5 months (95%CI 2–7). Median PFS, 6m-PFS, OS, and 2y-OS were 6 months (95%CI 4–9), 51%, 15 months (10–19), and 30%, respectively. A second surgical complete remission (CR2) was achieved in 26 (51%) patients. After multivariate analysis, previous use of ifosfamide (HR 2.007, p = 0.034) and CR2 (HR 0.126, p < 0.001) showed a significant correlation with PFS and OS, respectively. No significant correlation was found between outcomes and PARP1 or gene mutations. Conclusions: HD-IFO should be considered as the standard first-line treatment option in relapsed osteosarcoma and control arm of future trial in this setting.